Accuracy of X-ray with perfusion scan in young patients with suspected pulmonary embolism. Issue 2 (August 2015) - van Es, J.; Douma, R.A.; Hezemans, R.E.L.; Penaloza, A.; Motte, S.; Erkens, P.G.M.; Durian, M.F.; van Eck-Smit, B.L.F.; Kamphuisen, P.W.
Abstract Background Computed tomography pulmonary angiogram (CTPA) has become the standard test in the diagnostic workup of patients with suspected pulmonary embolism (PE). However, young patients may have an increased risk of cancer with CTPA. Perfusion scanning combined with chest X-ray (X/Q) may offer an adequate alternative, but has never been prospectively validated. We directly compared this strategy with CTPA in patients aged ≤ 50 years with suspected PE. Methods Consecutive patients with a likely clinical probability or an abnormal D-dimer level underwent both CTPA and X/Q. Two trained and experienced nuclear physicians independently analyzed the X/Q-scans. The accuracy of X/Q according to the PISAPED criteria was calculated in terms of sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Results Seventy-six patients were included, with a PE rate of 33%. The inter-observer agreement for X/Q-scan reading was high (κ = 0.89). After consensus reading, 21 patients (28%) were categorized as 'PE present', 53 (70%) as 'PE absent', and two (2.6%) as 'non-diagnostic'. In 22%, there was a discrepancy between the X/Q-scan and CPTA for the diagnosis or exclusion of PE. The PPV and NPV were 71% and 83%, respectively. Conclusion In patients with a high risk of PE, a diagnostic strategy of chest X-ray and perfusion scanning using the PISAPED criteria seems less safe than CTPA. Additional studies should further investigate this diagnostic algorithm.